2015
DOI: 10.1039/c5ay01852h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a green method for separation and identification of the degradation impurity of isoniazid by SFC-MS/MS

Abstract: To produce an eco-friendly stability indicating method, the reaction solutions containing degradation products of isoniazid were used for separation and optimized by varying the supercritical fluid chromatography (SFC) conditions. A mixture of supercritical carbon dioxide (SC-CO 2 ) (85%) and modifier dichloromethane : methanol : ethyl acetate : formic acid (70 : 30 : 0.5 : 0.1 v/v/v/v) (15%) was used as a mobile phase and separation was achieved using a C-18 column. The degradation products separated at relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[28][29][30][31] Therefore, 0.1% formic acid was added to the methanol for the SFC/MS work. It is reported that when a volatile acid (like formic acid) is added to the mobile phase, it will increase the positive ion of the analyte, which is most helpful in MS/MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31] Therefore, 0.1% formic acid was added to the methanol for the SFC/MS work. It is reported that when a volatile acid (like formic acid) is added to the mobile phase, it will increase the positive ion of the analyte, which is most helpful in MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that when a volatile acid (like formic acid) is added to the mobile phase, it will increase the positive ion of the analyte, which is most helpful in MS/MS. [28][29][30][31] Therefore, 0.1% formic acid was added to the methanol for the SFC/MS work.…”
Section: Resultsmentioning
confidence: 99%
“…For pharmaceutical and food samples, CO 2 is a suitable solvent for extraction because of its non-toxicity, low critical temperature, and rapid de-solvating of extracted compounds [31][32][33]. Solvating power of SCFs could be changed by varying some variables such as temperature and pressure.…”
Section: Sfe In Food and Pharmaceutical Analysismentioning
confidence: 99%